1976
DOI: 10.1136/gut.17.9.685
|View full text |Cite
|
Sign up to set email alerts
|

Exocrine pancreatic function in juvenile-onset diabetes mellitus.

Abstract: Hepatocellular carcinoma is an aggressive cancer with poor prognosis. Fibroblast growth factor 19, a member of the fibroblast growth factor family, is a ligand for fibroblast growth factor receptor 4. Moreover, it plays a crucial role in the progression of hepatocellular carcinoma. ASP5878 is a novel inhibitor of fibroblast growth factor receptors 1, 2, 3, and 4 that is under development. It inhibits fibroblast growth factor receptor 4 kinase activity with an IC 50 of 3.5 nmol/L. ASP5878 potently suppressed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
92
1
6

Year Published

1984
1984
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(108 citation statements)
references
References 17 publications
9
92
1
6
Order By: Relevance
“…These results are in agreement with previously published data (24,25). The lower trypsin levels in plasma of insulin-dependent diabetic patients have been attributed to a decrease of exocrine pancreatic secretion in this disease (26,27). Even if a ratio reg protein/trypsin was considered in this study, the highest values were observed mainly in long-standing diabetes, and not in the more active periods of diabetogenesis.…”
Section: Discussionsupporting
confidence: 82%
“…These results are in agreement with previously published data (24,25). The lower trypsin levels in plasma of insulin-dependent diabetic patients have been attributed to a decrease of exocrine pancreatic secretion in this disease (26,27). Even if a ratio reg protein/trypsin was considered in this study, the highest values were observed mainly in long-standing diabetes, and not in the more active periods of diabetogenesis.…”
Section: Discussionsupporting
confidence: 82%
“…This conclusion is substantiated by clinical studies on the exocrine secretory capacity of the pancreas in chronic Type I diabetes demonstrating decreased secretion of enzymes [32][33][34][35][36]. Frier et al found that the preservation of pancreatic function correlates with the duration of diabetes [32] and the persistence of B-cell secretory activity measured by C-peptide levels [33]. Domschke et al [34] and Lankisch et al [35], however, were not able to confirm these correlations.…”
Section: Discussionmentioning
confidence: 56%
“…The secretory capacity of not only amylase (Frier et al, 1976;Lankisch et al, 1982) but also chymotrypsin (Yokoyama et al, 1982) or trypsin (Frier et al, 1980) is low. The size of the pancreas measured by computed tomography in juvenile-onset IDDs is much smaller than that in age matched non-insulin dependent diabetics (Ohno et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…of exocrine pancreatic function has been reported in patients with juvenile-onset insulin dependent diabetes mellitus (Frier et al, 1976;Lankisch et al, 1982;Yokoyama et al, 1982). The extent to which exocrine pancreatic function is preserved correlates with the persistence of B-cell secretory activity measured by Cpeptide levels, or with the duration of the disease (Yokoyama et al, 1982;Frier et al, 1978).…”
Section: Insufficiencymentioning
confidence: 99%